Network embeddedness and innovation performance of small and medium enterprises: Mediating role of absorptive capacity - Omer Azam; Hafiz Ghufran Ali Khan; Imran Ghafoor Chaudhry (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2022)
Aim of this study is to identify the effect of network embeddedness on innovative performance of small and medium enterprise (SME) firms. Further, this research also seeks the mediating role of absorptive capacity of SME firms based upon a resource-based view and social network theory. Data is analyzed by applying multiple linear regression and structural equation modeling using SPSS and AMOS respectively. Findings of this study reveal that network embeddedness and innovation performance are positively related and absorptive capacity fully mediates between network embeddedness and innovation performance. This study explains how and when network embeddedness positively influences innovation performance for developing new products and creating new technologies for competing with other players of SME firms based upon the theoretical concept of social network theory and resource-based view.
Keywords: 330; Structural embeddedness; network embeddedness; relative embeddedness; absorptive capacity; SMEs; innovative performance